Chapter Monitoring changes over a 10-year period, through vegetation maps, in a coastal site in Apulia region (southeastern Italy) - Mantino, Francesca (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study aims to detect, analyze, and evaluate the habitat changes, between 2010 and 2020, occurred in the Mediterranean wetland system of "Zone Umide della Capitanata e Paludi presso il Golfo di Manfredonia". We classified habitats in 2020 using Eunis classification and we compared the obtained map with the Eunis map of 2010, obtained using the same approach, in terms of class area, Magnitude of Changes and the corresponding Trend Percentage of Change. It emerged that expansion of agricultural activities and alterations of the hydrological regime are behind most of the observed changes.